Magnetic resonance imaging of painful metal-on-metal total hip replacement. - Nikolaou, Vassilios S; Petit, Alain; Khoury, Viviane; Blain-Pare, Etienne; Zukor, David J; Huk, Olga L; Antoniou, John (Eur J Orthop Surg Traumatol, 2015)
Consecutive patients that had primary metal-on-metal (MoM) or metal-on-polyethylene (MoP) hip arthroplasty were prospectively enrolled to this study. All operated hips were evaluated with MRI by one radiologist who was blinded to the radiographic findings and clinical symptoms. Three groups of patients were formed: (1) thirteen MoM THRs in 13 patients with groin pain (Group 1), (2) ten MoM THRs in 10 patients with no pain (Group 2), (3) five MoP THRs in 4 patients without pain (control group). Abnormal MRI findings were distributed in all groups in a balanced way, irrespective of the patients' symptoms, prostheses, or metal ion levels. Two patients from Group 1 and one patient of Group 3 (control group) were diagnosed with a large periprosthetic mass (pseudotumor).
Keywords: Aged; Aged, 80 and over; Arthralgia; Arthroplasty, Replacement, Hip; Chromium; Cobalt; Female; Humans; Magnetic Resonance Imaging; Male; Metal-on-Metal Joint Prostheses; Middle Aged; Polyethylene; Prospective Studies; Single-Blind Method